The examination of sensitivity to corrosion of nickel-titanium and stainless steel endodontic instruments in root canal irrigating solutions - Popović Jelena; Radenković Goran; Gašić Jovanka; Živković Slavoljub; Mitić Aleksandar; Nikolić Marija; Barac Radomir (Chemical Industry and Chemical Engineering Quarterly, 2016)
The application of irrigating solutions is essential in chemomechanical treatment of tooth root canal. However, chemical and electrochemical aggressiveness of the solutions, which directly act on instruments, may damage their surface. The aim of this study was to investigate the sensitivity of the nickel-titanium (Ni-Ti) and stainless steel endodontic files to corrosive action of the sodium hypochlorite (NaOCl), chlorhexidine gluconate (CHX) and ethylenediamine tetraacetic acid (EDTA). Testing of sensitivity to corrosion of the instruments was performed by dynamic potentiometric method. Measurements were made in 5.25% NaOCl, 0.2% CHX and 17% EDTA. Ni-Ti instruments immersed in 5.25% NaOCl showed the most intensive corrosive changes and the lowest value of pitting potential of 1.1V. Stainless steel instruments immersed in 5.25% NaOCl showed higher value of pitting potential of 1.5V. Stainless steel instruments immersed in 0.2% CHX showed lower corrosive surface changes and higher value of pitting potential of 1.6V, whereas Ni-Ti instruments immersed in 0.2% CHX showed the pitting potential of 1.9V. The corrosion was not observed in both types of instruments after immersion in 17% EDTA. The use of 5.25% NaOCl and 0.2% CHX may cause severe surface corrosion of Ni-Ti and stainless steel endodontic files. [Projekat Ministarstva nauke Republike Srbije, br. 175102]